Efficient gene delivery to human umbilical cord mesenchymal stem cells by cationized Porphyra yezoensis polysaccharide nanoparticles - Yu Q (Dove Medical Press, 2015)
Qingtong Yu,1,2 Jin Cao,2 Baoding Chen,3 Wenwen Deng,2 Xia Cao,2 Jingjing Chen,2 Yan Wang,2 Shicheng Wang,2 Jiangnan Yu,2 Ximing Xu,2 Xiangdong Gao1 1School of Life Science and Technology, China Pharmaceutical University, Nanjing, 2Department of Pharmaceutics, School of Pharmacy and Center for Drug/Gene Delivery and Tissue Engineering, Jiangsu University, 3Department of Medical Ultrasound, Affiliated Hospital of Jiangsu University, Zhenjiang, People’s Republic of China Abstract: This study centered on an innovative application of Porphyra yezoensis polysaccharide (PPS) with cationic modification as a safe and efficient nonviral gene vector to deliver a plasmid encoding human Wnt3a (pWnt3a) into human umbilical cord mesenchymal stem cells (HUMSCs). After modification with branched low-molecular-weight (1,200 Da) polyethylenimine, the cationized PPS (CPPS) was combined with pWnt3a to form spherical nanoscale particles (CPPS-pWnt3a nanoparticles). Particle size and distribution indicated that the CPPS-pWnt3a nanoparticles at a CPPS:pWnt3a weight ratio of 40:1 might be a potential candidate for DNA plasmid transfection. A cytotoxicity assay demonstrated that the nanoparticles prepared at a CPPS:pWnt3a weight ratio of 40:1 were nontoxic to HUMSCs compared to those of Lipofectamine 2000 and polyethylenimine (25 kDa). These nanoparticles were further transfected to HUMSCs. Western blotting demonstrated that the nanoparticles (CPPS:pWnt3a weight ratio 40:1) had the greatest transfection efficiency in HUMSCs, which was significantly higher than that of Lipofectamine 2000; however, when the CPPS:pWnt3a weight ratio was increased to 80:1, the nanoparticle-treated group showed no obvious improvement in translation efficiency over Lipofectamine 2000. Therefore, CPPS, a novel cationic polysaccharide derived from P. yezoensis, could be developed into a safe, efficient, nonviral gene vector in a gene-delivery system. Keywords: Porphyra yezoensis, nanoparticle, nonviral vector, human umbilical cord mesenchymal stem cells, Wnt3a